MicroRNA Profiling of Self-Renewing Human Neural Stem Cells Reveals Novel Sets of Differentially Expressed microRNAs During Neural Differentiation In Vitro - Fedorova, Veronika; Amruz Cerna, Katerina; Oppelt, Jan; Pospisilova, Veronika; Barta, Tomas; Mraz, Marek; Bohaciakova, Dasa (Stem cell reviews and reports, 2023)
The involvement of microRNAs (miRNAs) in orchestrating self-renewal and differentiation of stem cells has been revealed in a number of recent studies. And while in human pluripotent stem cells, miRNAs have been directly linked to the core pluripotency network, including the cell cycle regulation and the maintenance of the self-renewing capacity, their role in the onset of differentiation in other contexts, such as determination of neural cell fate, remains poorly described. To bridge this gap, we used three model cell types to study miRNA expression patterns: human embryonic stem cells (hESCs), hESCs-derived self-renewing neural stem cells (NSCs), and differentiating NSCs. The comprehensive miRNA profiling presented here reveals novel sets of miRNAs differentially expressed during human neural cell fate determination in vitro. Furthermore, we report a miRNA expression profile of self-renewing human NSCs, which has been lacking to this date. Our data also indicates that miRNA clusters enriched in NSCs share the target-determining seed sequence with cell cycle regulatory miRNAs expressed in pluripotent hESCs. Lastly, our mechanistic experiments confirmed that cluster miR-17-92, one of the NSCs-enriched clusters, is directly transcriptionally regulated by transcription factor c-MYC.
Keywords: mikro RNA; Gene Expression Profiling; miRNA sequencing; Embryonic Stem Cells; embryonální kmenové buňky; microRNA; buněčná diferenciace; MicroRNAs; nervové kmenové buňky; Human pluripotent stem cells; lidé; Neural stem cells; Neural Stem Cells; stanovení celkové genové exprese; Humans; Cell Differentiation; Cell cycle